Deformation and fatigue behaviors of carburized automotive gear steel and predictions (Fracture and Structural Integrity, 2016)
The fatigue behavior of carburized components such as automotive transmission gears is very complex due to hardness and microstructure difference, residual stresses and multi-axial stress states developed between the case and the core. In addition, automotive gears in service, commonly used in helical type, are actually subjected to complex stress conditions such as bending, torsion, and contact stress states. This study presents experimental and analytical results on deformation behavior of carburized steels, widely used in automotive gears, under cyclic stress conditions including axial and torsion loadings. Axial fatigue tests and rotating bending fatigue tests are also included. Predictions of cyclic deformation and fatigue behaviors of the carburized steel with two-layer model are compared with experimental results. The carburized steel investigated in this study exhibited cyclic softening under both axial loading and torsional loading. Predicted results with simple two-layer model for the cyclic deformation and fatigue behaviors were comparatively similar to the experimental data.
Keywords: Carburizing; Case hardening; Gear steel; Cyclic softening; Fatigue; Prediction